Analisis Kualitas Selai Organik Dari Buah Mengkudu Sebagai Produk Bisnis Skala Rumahan - Tania Adila; Novsa Fakhira (Jurnal Sains Boga, 2022)
Noni is one of the most abundant fruits in Indonesia. Noni trees that bear fruit every season need to be further processed to reduce the amount of fruit wasted. In addition, the fruit contains many health benefits so it would be very good if used as food. One of the efforts to use noni can be done by creating a product in the form of organic jam. This study aims to determine the quality of noni fruit jam using the same level of maturity in terms of taste, color, texture and aroma. The data collection method used in this research is the organoleptic test method, documentation and questionnaires. This quantitative and qualitative research was also obtained from the power of the assessment test instrument. The respondents in this study amounted to 70 people consisting of the community around the research site (North Bogor) including IPB students, school students, motorcycle drivers and housewives. The results of the research based on organoleptic tests showed that organic noni jam products were acceptable in the market with a taste score of 275 (tasty), texture 240 (chewy), aroma 195 (quite delicious), and color 188 (quite attractive)